THE USE OF MY DICTIONARY APPLICATION TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Iman Santoso; Andriyadi Andriyadi (Eltin Journal : Journal of English Language Teaching in Indonesia, 2019)
The purpose of this study was to know the result of improving students’ vocabulary mastery by using My Dictionary Application. This research used Quasi-Experiment design. This research involved two classes IX A and IX B as the sample of this research. IX A was selected as experimental class and IX B was selected as control class. In the experimental class, vocabulary was taught by using My Dictionary Application. While, in the control class, vocabulary was taught by using with the conventional media. The data was collected from pre-test dan post test. Then , the data obtained was analyzed by using SPSS. The result of the study showed that teaching vocabulary by using My Dictionary Application significantly improving students’ vocabulary. The findings showed that the mean of Experiment class students was 25.20, and the control class means score was 21.40. After treatment given, there is a significant increase. The means of the Experiment class is 48.40, and the class of the control class is 30.50. After that compared between posttest result class experiment with control class result is t (result the research) = Σ X1 - Σ X2 = t = 48, 40 - 30, 50 = 19.00. Where Σ X1 (experiment class)> Σ X2 (control class). This means that the use of my dictionary application gives effect to vocabulary mastery of students.